Effect of fermentation on anti-nutritional factors and in vitro protein hydrolysis of Vigna subterranea (L) Verdc. (Bambara groundnut) - Tee, Ann Jo (2025)
Vigna subterranea (L) Verdc. (Bambara groundnut) (BG) remains underutilised due to the hard-to-cook (HTC) seed and the presence of anti-nutritional factors (ANF) which negatively affect protein digestibility. Many thermal and physical processing methods have been conventionally used to alleviate the HTC and ANF in legumes. However, these processing methods often involve complex procedures with high cost and energy consumption, while causing unavoidable losses of heat-sensitive and water-soluble nutrients. Fermentation offers an affordable and environmentally friendly method of processing the legumes into nutritious and digestible products. Hence, the current research project aimed to investigate the effect of bacterial and fungal fermentation in reducing the ANF (trypsin inhibitor, phytate and tannin) and enhancing the protein hydrolysis of BG. This project started with a back-slopping method using three Malaysian fermented foods (Tempeh, Tapai ubi and Tapai pulut) as starters for the fermentation of BG. All starters successfully initiated the fermentation process, and a total of seven fungi (Candida akabanensis TEMM-1 to TEMM-5, Diutina mesorugosa TEMS-1, Kodamaea ohmeri TAUM-1) and five bacteria (Leuconostoc mesenteroides TAUM-2, TAUM-3, TAPS-2 and TAPS-3, Pediococcus pentosaceus TAPS-1) were isolated from the fermented foods and identified using 16S rRNA gene sequence analysis. All twelve isolates demonstrated the absence of hemolytic and DNase activity, suggesting that if consumed will not pose a threat to health. To evaluate the effect of fermentation on the ANF and proximate composition of BG, L. mesenteroides TAPS-3 isolated from Tapai pulut was selected as the starter culture. After 24 h of fermentation at 37°C, TAPS-3 successfully reduced the tannin and phytate content (p < 0.05), and improved the protein content by 9.2% with no significant reduction in the remaining nutrients. With this promising finding, a subsequent study was performed using six selected bacterial and fungal isolates for inducing BG fermentation and evaluating their effectiveness in tannin and phytate reduction. Five isolates successfully induced the BG fermentation and reduced the ANF to varying degrees (p < 0.05). Among them, the bacterium P. pentosaceus TAPS-1 produced the highest reductions of tannin (21.2%) and phytate (12.8%). While the fungus C. akabanensis TEMM-1 achieved a maximum phytate reduction of 11.2% at 24 h of fermentation. Both TAPS-1 and TEMM-1 isolates with greater tannin and phytate removal efficiency were subjected to the single- and mixed-starter culture(s) BG fermentations, followed by the INFOGEST in vitro gastrointestinal digestion to determine the extent of protein hydrolysis. Two substrates, non-sterile BG (NsBG) and sterile BG (SBG), were used in this study, and the six fermentation approaches successfully enhanced the protein hydrolysis of these substrates. The fermentation using solely bacterium P. pentosaceus TAPS-1 was most effective in hydrolysing the proteins of NsBG and SBG. When compared to the fungal fermentation, the bacterial fermentation of NsBG (NsBG-B) exhibited the highest degree of protein hydrolysis with more primary amines being liberated (p < 0.05). The NsBG-B also retained most of the amino acids (except serine) at levels comparable to the controls after in vitro digestion. Hence, this study suggests that bacterial fermentation could be a feasible approach for processing the underutilised BG by reducing its undesired ANF and enhancing the protein digestibility. This fermentation approach could potentially be used to process other HTC legumes to improve their protein hydrolysis and promote wider utilisation.